Update on Thyroid Hormone Levels and Thyroid Dysfunction in the Korean Population Based on Data from the Korea National Health and Nutrition Examination Survey VI (2013 to 2015) - Jae Hoon Chung (Endocrinology and Metabolism, 2020)
In 2017, the first Korean nationwide data on serum thyroid stimulating hormone (TSH) levels, serum free thyroxine (fT4) levels, and urinary iodine concentration (UIC) were published based on a population of 7,061 Koreans who participated in the Korea National Health and Nutrition Examination Survey VI. The mean TSH level was 2.16 mIU/L, with a reference interval of 0.59 to 7.03 mIU/L (men 2.09 mIU/L, women 2.24 mIU/L, P<0.001). A U-shaped association was found between serum TSH levels and age. The mean fT4 level was 1.25 ng/dL, and its reference interval was 0.92 to 1.60 ng/dL (men 1.29 ng/dL, women 1.20 ng/dL, P<0.0001). Serum fT4 levels decreased with age (P for trend <0.0001). Serum thyroid peroxidase antibody (TPOAb) was detected in 7.30% of participants (men 4.33%, women 10.62%). TPOAb titers tended to increase with age, and were higher in women than in men. The median UIC was 294 µg/L, and UIC showed a U-shaped relationship with age. According to the World Health Organization recommendations, only 23% of participants were in the adequate range of iodine intake, while 65% were in the above requirements or excessive, and 12% in insufficient. The prevalence of overt hyperthyroidism and hypothyroidism in Koreans was 0.34% to 0.54% and 0.73% to 1.43%, respectively.